Study guides

☆☆

Q: What is the simplist for of 6x plus 4(2x plus 4)-3?

Write your answer...

Submit

Still have questions?

Related questions

It is: 42x+30x^2

-18x2-42x=-6x(3x+7)

8x-3+6x-1 = 12x+614x-4 = 12x+614x-12x = 6+42x = 10x = 5

x=7

5x + 32 = 11x - 105x - 11x = -10 - 32-6x = -42x = 7

x3 + 13x2 + 42x = x(x2 + 13x + 42) = x(x2 + 6x + 7x + 42) = x[x(x + 6) + 7(x + 6)] = x(x + 7)(x + 6)

4x - 5 + 2x = 376x - 5 = 376x = 37 + 56x = 42x = 42 / 6x = 7

-8 + 7(6x) + 3 = -7x - 5 - 1-8 + 42x + 3 = -7x - 5 - 142x - 8 + 3 = -7x - 5 + (-1)42x - 5 = - 7x - 642x + 7x - 5 + 5 = - 7x + 7x - 6 + 549x = -149x/49 = -1/49x = -1/49

2x + 15 = 8x + 43 -6x = 28 x = -6 / 28 = -3 / 14

-6x^2 - 78x - 252 Improved answer: -6x+6x+7 When simplified = 7

7+10+(-6x)=17-6x

The answer is 258x

People also asked